Haemostatic activation and Inflammatory response after three methods of treatment of great saphenous vein incompetence. (April 2014) - Dzieciuchowicz, L; Espinosa, G; Páramo, J A
Objective: The purpose of this study was to compare the activation of haemostasis and inflammatory response after three different methods of treatment of great saphenous vein (GSV) incompetence. Material and methods: Forty-five patients with GSV incompetence were assigned to one of the three types of treatment: high ligation and stripping (HL&S), radiofrequency ablation with ClosureFast (RFA) and endovenous laser ablation (EVLA) with 810 nm diode laser with miniphlebectomy if required. Peripheral blood samples were obtained in the morning before the surgery and 24 hours and 10 days after the procedure. The concentrations of C-reactive protein (CRP), D-dimer, prothrombin fragment 1+2 (F1 + 2), antigen of tissue plasminogen activator (t-PA) and von Willebrand factor (vWF) antigen and activity of plasminogen activator inhibitor (PAI-1) were determined. The results were statistically analysed with SPSS for Windows 15.0. Results: Thirty-eight patients completed the study: 13 from RFA, 14 from EVLA and 11 from HL&S group. The baseline data did not differ among groups. There was a significant increase of D-dimer in HL&S group after 24 hours ( P = 0.002). The changes in RFA and EVLA groups did not show statistical significance ( P = 0.092). PAI-1 decreased in RFA patients after 24 hours ( P = 0.02), did not change in EVLA patients, and tended to increase after HL&S (P = 0.08). The highest CRP increase was observed in HL&S group ( P = 0.003). No significant changes in F1 + 2, t-PA and vWF were observed in any group of patients at 24 hours. At 10 days, a further significant increase of D-dimer ( P = 0.04) and CRP ( P = 0.018) concentrations in HL&S but not RFA and EVLA patients was observed. Conclusions: Endovenous thermal ablation is associated with significantly less activation of haemostasis and inflammatory response when compared with HL&S.